Role of Silver Nanoparticles (AgNPs) in Food Surface Packaging: Effects of AgNPs on Packaging (Biological Sciences - PJSIR, 2023)
Reliance on processed food increased in the late 90s and the need for fresh food with a long shelf-life was felt according to the interest of consumers. Antibacterial effect of the papers used in food packaging extend the shelf-life of the products and food to keep them in healthier conditions. Binders used in paper coating provide a good nutrient medium for bacteria. As an antibacterial agent, AgNPs have been used significantly in health industry and in food storage and packaging, textile coatings and also in several environmental applications. They have also been used as antibacterial agent in medical device and in home appliance fumigation, as well as water treatment cotton fiber. AgNps from food packaging may be un-intentionally released into food and end up in the gastrointestinal tract. As a result, human exposure to AgNPs is increasing and it is critical to understand their negative effects. However, nano- particles migrating to food are not wholly studied by researchers. This review examines the most research findings on the use of AgNPs to protect food products against the most common food pathogens.